EFFECT OF INTRAUTERINE IMMUNOTHERAPY ON UTERINE CELLULAR DYNAMICS AND CONCEPTION RATE IN ENDOMETRITIC COWS - SARMA, D K; SINGH, BALRAJ; SINGH, M P; TIWARY, B K; SINHA, M P (The Indian Journal of Animal Reproduction, 2023)
The efficacy of three intrauterine (IU) immunomodulators was investigated in endometritis of cross bred cows. ·Forty endometritic cows were divided into 4 groups (n=10) and marked as T1 , T2 , T3 and T4 T1 cows received E. coli lipopolysaccharide (LPS). Oyster Glycogen (OG) and Autologus Plasma (AP) were used in group T2 and T3, respectively. T4 was kept as control with single infusion of 60ml Phosphate Buffer Solution (PBS, pH-7.2). After 24 hours of treatments significant (P<0.01) increase of neutrophils and lymphocytes in uterine flushing were observed with significant (P<0.01) reduction in epithelial denudation in all treatment groups. Conception rate increased significantly (P<0.01) in groups T1 , T2 , and T3 . The results indicated that intrauterine immunomodulators can be used as alternative to antibiotic in resolving endometritis in cows.